2014
DOI: 10.4304/tpls.4.5.1093-1100
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Problem-solving Trait and the Performance on C-test

Abstract: Abstract-Individuals attend language classrooms with miscellaneous personal attributes which are going to influence learners' test performance. Therefore, individual differences play an important role in sources of variance in test scores. This paper aims at investigating the effect of problem solving on the language ability obtained through C-tests. To this end, 70 EFL learners were randomly chosen and they were required to fill Parker's Problem-Solving Style Questionnaire (PSSQ). Simultaneously, they were gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…Results indicated that there is no significant relationship between learners' Production-based preference for assessment and Pragmatist (r=.09 p>.05). Obtained results were in contrast with what Ghodrati, Bavandian, Moghaddam, and Attaran (2014) gained in their study. They believed that there is a high correlation between cloze type of test and elements of problem solving.…”
Section: Discussioncontrasting
confidence: 92%
“…Results indicated that there is no significant relationship between learners' Production-based preference for assessment and Pragmatist (r=.09 p>.05). Obtained results were in contrast with what Ghodrati, Bavandian, Moghaddam, and Attaran (2014) gained in their study. They believed that there is a high correlation between cloze type of test and elements of problem solving.…”
Section: Discussioncontrasting
confidence: 92%
“…", and "I can remain calm when facing difficulties because I can rely on my coping abilities." Self-efficacy is defined as people's beliefs about their capabilities to produce and perform [4], and it plays a critical role in how individuals think, feel and behave, and for that reason it seems that it is directly connected with the tasks of data analysis, the rational and intuitive aspects of the proposed tool; (e) The Problem Solving Styles Questionnaire (PSSQ) [16] with 20 items and 4 scales (i.e., PS-Sensing, PS-Intuitive, PS-Feeling, PS-Thinking [19]). For last two tools each concept embraces five questions that participants need to respond on a 5-point scale (1 = strongly disagree to 5 = strongly agree).…”
Section: Sampling and Proceduresmentioning
confidence: 99%